Oral Route as a Mechanism of Transmission of Chagas Disease - Castro Tenorio, Oliva (Mexican Journal of Medical Research ICSA, 2017)
Chagas disease or American trypanosomiasis is considered a neglected disease, and a public health problem, due to the high prevalence of the disease, as well as the high economic and social costs that it entails. There are different routes of transmission, the vector route being the main mechanism, although it can also be transmitted vertically, by transfusional transmission, by organ transplantation, laboratory accidents, and relatively new in its study, the oral route. This route is considered the oldest route of transmission, responsible for the preservation of the infection in a sylvatic way. Due partly to the decrease in the incidence of vector cases, and human activities, the oral route has been the mechanism that explains the acute outbreaks of Chagas' disease in different Latin American countries; together with its greater lethality, is that this via has become important. Early recognition of the disease is crucial in order to establish antiparasitic treatment as soon as possible, because it limits the evolution of the disease in most cases, so this research work has the objective of carrying out a bibliographic review of the oral route as a mechanism of transmission of Chagas' disease.